Apparent Specific Heat Measurements of Rabbit Artery during Freezing Phase Transition by DSC - 胥义; 周国燕; 胡桐记; 高才; 华泽钊 (Zhileng xuebao)
The apparent specific heat of rabbit artery during phase transition was measured using the Differential Scanning Calorimeter (DSC). Further, the effects of concentrations of cryoprotective agent (CPA) on apparent specific heat of rabbit artery were investigated. Experimental results show that the higher the concentration of dimethyl sulphoxide(DMSO) solution is, the lower the peak value of the apparent specific heat is. However, apparent specific heat is much higher after freezing phase transition due to the content of bound water increasing. According to experimental data, the existing approximate formula about apparent specific heat in the phase transition range was also corrected.